2020
DOI: 10.3390/su12187625
|View full text |Cite
|
Sign up to set email alerts
|

Creating Shared Value and Fan Loyalty in the Korean Professional Volleyball Team

Abstract: Creating shared value has been a new strategic management paradigm for professional sport teams around the world. However, despite the active participation of professional sport teams in creating a shared value program, research that addresses its effectiveness appears to be very limited. The present study investigates the influence of sport fans’ perceived creating shared value on team trust and fan loyalty and the moderating effects of sport fans’ altruism on the relationship between creating shared value an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 38 publications
2
17
0
2
Order By: Relevance
“…The researchers concluded that the positive perception of the community and the employees about the economic value of the CSV program transformed the reputation of the company into something positive and respectable. Kim et al, [15] also found that the sport fans' perceived economic value of a CSV program positively impacted the professional baseball team's image. The researchers that the CSV program could serve as an effective marketing strategy for the brand image enhancement of professional sport teams.…”
Section: Creating Shared Value and Brand Imagementioning
confidence: 99%
See 4 more Smart Citations
“…The researchers concluded that the positive perception of the community and the employees about the economic value of the CSV program transformed the reputation of the company into something positive and respectable. Kim et al, [15] also found that the sport fans' perceived economic value of a CSV program positively impacted the professional baseball team's image. The researchers that the CSV program could serve as an effective marketing strategy for the brand image enhancement of professional sport teams.…”
Section: Creating Shared Value and Brand Imagementioning
confidence: 99%
“…Along with active participation in CSV programs at the corporate level, studies related to the validity and reliability evaluation of CSV activities have been conducted. Prior relevant research supports that consumers perceive a company's economic value, which refers to corporate profit maximization by improving product and service quality as a firm supplies products and services necessary to consumers [15] as an essential factor in successfully implementing a CSV program. It enhances productivity, such as compliance with corporate ethics and transparent management [20].…”
Section: Creating Shared Value and Brand Imagementioning
confidence: 99%
See 3 more Smart Citations